2003
DOI: 10.2140/pjm.2003.211.157
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic properties of Volterra operator

Abstract: A bounded linear operator T defined on a Hilbert space H is said to be supercyclic if there exists a vector x ∈ H such that the set {λT n x : n ∈ N, λ ∈ C} is dense in H. In the present work, two open questions posed by N. H. Salas and J. Zemánek respectively, are solved. Namely, we will exhibit that the classical Volterra operator V and the identity plus Volterra operator I + V are not supercyclic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Our approach has nothing in common with the ones from [3] or [14]. In [14] it is shown that positive operators commuting with V are not weakly supercyclic and, naturally, the proof employs positivity argument.…”
Section: Theorem 11 Let 1 P < ∞ and T ∈ L(l P [0 1]) Be Such That mentioning
confidence: 99%
See 4 more Smart Citations
“…Our approach has nothing in common with the ones from [3] or [14]. In [14] it is shown that positive operators commuting with V are not weakly supercyclic and, naturally, the proof employs positivity argument.…”
Section: Theorem 11 Let 1 P < ∞ and T ∈ L(l P [0 1]) Be Such That mentioning
confidence: 99%
“…We refer to the survey [18] for the details. Weak supercyclicity was introduced by Sanders [24] and studied in, for instance, [14,15,20,22,25,27]. Gallardo and Montes [8], answering a question raised by Salas, demonstrated that the Volterra operator…”
Section: C(t ) = {S ∈ L(x) : [T S] = 0}mentioning
confidence: 99%
See 3 more Smart Citations